GEDUNG APRESIASI SENI ANAK BERKEBUTUHAN KHUSUS DI BALIKPAPAN - Abdillah, Nur Fitri; Dahliani, Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
In the context of art, the perspective of ordinary people sees the work of Children With Special Needs (ABK) only based on compassion. Thus it is felt necessary to plan and design an art appreciation building to appreciate the work of ABK in Balikpapan. The design of this building aims to provide facilities for ABK as a means of artistic expression as well as a place to appreciate artistic talent that is in accordance with the character of ABK. The Experience concept and the Behavioral Architecture method were chosen as a solution to the problem of presenting sensory experiences of space users, especially ABK, whose application includes behavioral consideration.